Silver Nanocomposite Electrode Modified with Hexacyanoferrate. Preparation, Characterization and Electrochemical Behaviour Towards Substituted Anilines - Fenga, Paula Goncalves [UNESP]; Stradiotto, Nelson Ramos [UNESP]; Isabel Pividori, Maria (Wiley-Blackwell, 2011)
A novel conducting silver nanocomposite (nanoAg-GEC) material for electrochemical sensing of substituted anilines based on silver nanoparticles is presented. For the first time, the in situ growth of silver hexacyanoferrate nanoparticles (nanoAgHCF) on the surface of the silver nanocomposite electrodes was achieved. The surface morphology of the nanoAg-GEC electrode modified with hexacyanoferrate (nanoAgHCF-GEC) was investigated using scanning electron microscopy (SEM) coupled with energy-dispersive X-ray spectroscopy (EDX). The electrochemical behaviour of the nanoAgHCF-GEC electrode towards oxidation and reduction of substituted anilines (procaine and sulfamerazine) was investigated by cyclic voltammetry. The results showed a linear dependence in the concentration range studied for each class of sulfonamides.
Keywords: Graphite-epoxy silver nanocomposite; Silver nanoparticles; Silver hexacyanoferrate nanoparticles; Procaine; Sulfamerazine